Differences in IDO1+ dendritic cells and soluble CTLA-4 are associated with differential clinical responses to methotrexate treatment in rheumatoid arthritis - Malik, Anikó E.; Slauenwhite, Drew; McAlpine, Sarah M.; Hanly, John G.; Marshall, Jean S.; Issekutz, Thomas B. (Frontiers in Immunology, 2024)
Objective Antigen-presenting dendritic cells (DCs) and monocytes play an essential role in rheumatoid arthritis (RA) pathogenesis, however, their tolerogenic potential remains unclear. Herein, the tolerogenic profiles of DCs are characterized in treatment-naïve RA patients to determine their role to inflammatory arthritis management. Methods Thirty-six treatment-naïve RA patients were enrolled, of which 62% were non-responders to methotrexate (MTX) monotherapy based on disease activity score (DAS) after 6-months of therapy. DC and monocyte subset frequencies, activation (CD40, CD86, CD209 expression), and tolerogenic profile (intracellular indoleamine-2,3-dioxygenase [IDO1] and cytotoxic T lymphocyte antigen 4 [CTLA-4] expression) were examined in the baseline peripheral blood by multicolor flow-cytometry. Soluble CTLA-4 (sCTLA-4) levels in plasma were measured. Results DC subsets were decreased in RA compared to healthy controls (HC), and the frequency of conventional DCs (cDC) inversely correlated with inflammatory markers and improvement in disease activity. CD141+ cDC1s were the major IDO1-expressing cells. IDO1+cDC1s were reduced in RA patients compared to HC. The baseline frequency of IDO1+cDC1s inversely correlated with improvement in disease activity. CTLA-4 expression in CD1c+ cDC2s and monocytes was lower in RA patients compared to HC. Moreover, MTX-responders had a significantly lower frequency of IDO1+cDC1 cells and higher level of sCTLA-4 in the plasma compared to MTX non-responders. There was a strong predictive association of low IDO1+cDC1 cells, low sCTLA-4 and non-response to MTX. Conclusions Our findings reveal altered DC and monocytes immunophenotypes that are associated with RA pathology and treatment response. The frequencies of tolerogenic IDO1+cDC1s and the low level of sCTLA-4 are strongly associated with MTX non-responsiveness and therapeutic outcome. These results suggest that investigation of the association IDO1+cDC1 and sCTLA-4 with response to treatment may be more generalizable to other autoimmune diseases.